Plan de mantenimiento de la sala de calderas del Hospital de Apoyo Chepen - Cosanatan Flores, Adolfo (2017)
This research project is a proposed plan of Preventive Maintenance to Boiler Room Support Hospital Chepén since the institution currently has no such plan. The objective of this project is the implementation of a maintenance plan, using the scheduled preventive maintenance, as it is important to consider the maintenance of the boiler to ensure optimal operation. The boilers are a critical equipment within the institution as steam generation depend on other units to work as plant equipment, kitchen and laundry. In this paper the importance of routine maintenance, as a tool when carrying out a maintenance strategy is discussed. Preventive maintenance routines allow you to have a history, know the status of the boiler and its auxiliary equipment, as well as identify the causes of failures to correct them, thereby increasing the reliability and availability of equipment. In this work sheets or control sheets they were also designed to carry a detailed study of the activities performed, for example; Control tab for a team, work order, service order and activity reports. By launching this maintenance plan would be obtained as results optimization, reliability and safe operation of the boiler.